Glucagon-like peptide-2 protects the gastric mucosa via regulating blood flow and metabolites - Zhang, Jing; Ning, Jing; Hao, Xinyu; Han, Xiurui; Fu, Wei; Gong, Yueqing; Meng, Qiao; Ding, Shigang; Zhang, Jing (Frontiers in Endocrinology, 2022)
Refractory peptic ulcers remain a therapeutic challenge. The direct role of glucagon-like peptide-2 (GLP-2), a gastrointestinal hormone, in the gastric mucosa remains unclear. This study was conducted to evaluate the role of GLP-2 in gastric mucosal lesions and its underlying mechanism. Male Sprague–Dawley rats were divided into three groups and pretreated with GLP-2 by intraperitoneal injection for 30 min following intragastric administration of ethanol for 1 h. Pretreatment with GLP-2 significantly reduced ethanol-induced gastric mucosal lesions by improving the gastric mucosal blood flow examined using a laser Doppler flow meter, Guth Scale, hematoxylin-eosin staining, and two-photon microscopy. LC-MS/MS analyses showed that GLP-2 also maintained a steady state of linoleic acid metabolism. Taken together, GLP-2 defends the gastric mucosa against ethanol-induced lesions by improving gastric microcirculation and affecting linoleic acid metabolism.